Pengaruh Absensi Online “Talenta” dan Motivasi Terhadap Disiplin Kerja Karyawan PT Kia Karawang - Afriyan Deniro Gultom; N. Neni Triana; Thomas Nadeak (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study was made to determine the extent of the attendance technology system and work motivation provided by PT KIA Karawang to its employees in improving employee discipline in it. The analysis used in this study is to use independent variables, namely the "Talent" attendance system and work motivation, and the dependent variable, namely work discipline. This research included 85 employees from PT KIA Karawang and utilized multiple linear regression testing, alongside validity, reliability, classical assumption, and hypothesis testing techniques. The findings revealed that the Talent attendance system and work motivation together significantly and positively affect work discipline. However, when examined individually, the Talent Attendance System did not impact Work Discipline, whereas work motivation did have a positive and significant effect on work discipline.